PENGELOLAAN DANA DESA KEPADA APARAT DESA BANYUURIP KABUPATEN MAGELANG - Sukarniati, Lestari; Ramadhona Amalia Lubis, Firsty; Faudzi, Maman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This community service program held in Banyuurip Village, Tegalrejo Sub-district, Magelang Regency aims to provide knowledge to Banyuurip village officials about the system of managing village funds, monitoring village funds and the system of managing village funds through BUMDES. This service uses socialization and training methods which were carried out on March 9, 2023 and carried out by 2 lecturers along with 1 student. The service activities went smoothly and the participants were enthusiastic in following the material.